(untitled) (Journal of history-rus, 2022)
The interference of Afghanistan’s neighboring countries, in particular Pakistan, in the internal affairs of Afghanistan has been considered a major factor behind the continuity of the civil war. From the early stage of the war against the Soviets and PDPA regime, Pakistan became the headquarters of the political leaders of the mujahedeen parties, as well as the host of millions Afghan refugees. The Soviet invasion of Afghanistan caused the destabilization of the region. This regional instability resulted in US aid to the mujahedeen and the United States also agreed with Pakistan to be the conduit of arms and supply to mujahedeen groups in Afghanistan. The direct involvement of Pakistani military leaders and the ISI in the internal affairs of Afghanistan began with a failed coup led by Muslim Brothers of Afghanistan against President Daoud in the spring of 1974. After the coup crashed, many of the Muslim brothers escaped to Pakistan, where they received direct support from Zulfiqar Ali Bhutto’s regime. The Pakistani military, led by the commander of Pakistan’s Frontier Corps, Brigadier Nasirullah Babur, became involved in Afghanistan’s internal affairs. Therefore, Babur has been the leading advocate of Pakistan’s forward policy – direct intervention toward Afghanistan. The geopolitical perception of Pakistan in Afghanistan should be examined in the light of the developing situation and Pakistan’s persistent efforts to establish a pliable and subservient regime in Afghanistan. Therefore, despite United Nations and other regional and International powers efforts; because of Pakistan’s interferences, Afghanistan couldn’t succeed to reach a peacefully settlement; and, unfortunately the civil war continued till today.